Slow pyrolysis of empty fruit bunches to produce biochar: article - Ishak, Ahmad Ismi Zulfadli; Alias, Rusmi (2017)
The objective of this study were to convert the unwanted empty fruit bunches into biochar via slow pyrolysis. Then the characteristic of the biochar produced were studied. BET surface area, proximate analysis, Methylene blue adsorption, and XRD were perform to characterize the biochar produced. 50 gram of EFB were pyrolyzed under specific temperature with fix heating rate of 10oC/min. After reaching the desired temperature, the pyrolyzer were left to heat for an hour. Proximately, biochar of 700⁰C contain the least volatile matter with 7.58% while biochar of 500⁰C produced the biggest fixed carbon content at 56.02%. For surface area, the biochar that came from 700⁰C yield the biggest area with 10.354 m2/g. XRD shows that all of the samples is amorphous. For removal of methylene blue from aqueous solution, biochar that is produced at 500⁰C has the best adsorption capacity due to the facts that it able to remove up to 91% of the methylene blue.